The ion transport study in corn starch-NaHSO₃ based polymer electrolytes / Fatin Farhana Awang ... [et al.] - Awang, Fatin Farhana; Hassan, Mohd Faiz; Chan, Kok Sheng; Kamarudin, Khadijah Hilmun (Universiti Teknologi MARA, 2021)
In this work, different amounts of sodium bisulfite, NaHSO3 (5wt.% to 40wt.%), were dissolved in a corn starch polymer host to synthesize solid polymer electrolyte (SPE) using a solution casting technique. Then, the films prepared were characterized using non-destructive electrical impedance spectroscopy to determine SPE films' conductivity and electrical transport properties. The highest conductivity of the sample at ambient temperature was recorded at 15wt. % of NaHSO3 with a value of 2.22 × 10-4 Scm-1. Moreover, the ion transport parameters at room temperature are found to be 2.41 × 10-7 cm2 s-1, 9.39 × 10-6 cm2 V-1s-1, 1.70 × 1019 cm-3 for D, µ and n, respectively. The conductivity of the samples was found dependent on diffusion coefficient, D and mobility, µ of ions.